Synergistic Improvement of Carbohydrate and Lignin Processability by Biomimicking Biomass Processing - Li, Man; Liu, Zhi-Hua; Hao, Naijia; Olson, Michelle L.; Li, Qiang; Bhagia, Samarthya; Shinde, Somnath; Kao, Katy C.; Ragauskas, Arthur J.; Xie, Shangxian; Yuan, Joshua S. (Frontiers in Energy Research, 2021)
The sustainability and economic feasibility of modern biorefinery depends on the efficient processing of both carbohydrate and lignin streams for value-added products. By mimicking the biomass degradation process in white-rote fungi, a tailored two-step fractionation process was developed to maximize the sugar release from switchgrass biomass and to optimize the lignin processability for bioconversion. This process was named as F2O (Formic Acid: Fenton:Organosolv) and achieved high processability for both carbohydrate and lignin. Specifically, switchgrass pretreated by F2O process had a 99.6% of the theoretical yield cellulose release. The fractionated lignin was also readily processable by fermentation via Rhodococcus opacus PD630 with a lipid yield of 1.16g/L. SEM analysis confirmed the fragmentation of switchgrass fiber and the cell wall deconstruction. 2D-HSQC NMR further revealed cleavage of aryl ether linkages (β-O-4) in lignin components. These results revealed the mechanisms for the efficient sugar release and lignin bioconversion. F2O process demonstrated effective mimicking of natural biomass utilization system and paved a new path for co-optimization of lignin and carbohydrate processability in next generation lignocellulosic biorefinery.